Real standards of living and public support for children: A cross-national comparison - Timothy Smeeding (Luxembourg Income Study (LIS), 2002)
Most cross-country comparisons of living standards focus on real Purchasing Power Parities (PPP) adjusted Gross Domestic Product (GDP) per person. These measures provide no variance in living standards within the nation, nor do they account for the amount of real incomes that families actually have to spend for themselves and their children. The Luxembourg Income Study (LIS) household microdata for 13 nations and Organization for Economic Cooperation and Development (OECD) PPP's and noncash benefit data are used to examine differences in the standard of living among children at various points in the income distribution. We include the value of noncash benefits for health care and education as well as money, and determine the value of public sector benefits compared to taxes paid for social transfers by this group. The results indicate a wide range of differences in levels of economic resources and support for children within, as well as between, nations. The levels of benefits, net of taxes paid, vary considerably across the income distribution in all countries, with noncash benefits for health and education playing a crucial role in determining which families are net beneficiaries or net taxpayers. The implications of these findings for equality of opportunity and for public policy, particularly in the United Kingdom and the Unites States, are drawn in conclusion.
Keywords: 330; Lebensstandard; Kinder; Jugendpolitik; EU-Staaten; Norwegen; Australien; USA; Kanada